Comprehensive Management of Pediatric Epidural and Subdural Hematomas Following Traumatic Brain Injury: A Case Report - Sari, Francisca Wuri Anzaz; Widarta, Oskar Ady (Jurnal Ners, 2024)
This case report details the management and implications of a 13-year-old male patient who presented with Epidural Hematoma (EDH) and Subdural Hematoma (SDH) following a traumatic brain injury sustained from a fall. The patient's treatment involved decompressive craniotomy to relieve intracranial pressure and reduce the risk of further brain damage, followed by cranioplasty to reconstruct the cranial vault. The case highlights the complexities involved in pediatric neurosurgery, especially in managing EDH and SDH, which are common yet critical conditions in traumatic brain injury cases. These hematomas, while distinct in their location and nature, share a common etiology in trauma and require prompt and effective surgical intervention. The importance of decompressive craniotomy in such cases is emphasized, particularly for alleviating increased intracranial pressure and minimizing additional cerebral injury. However, the potential postoperative complications, including cerebrospinal fluid leaks, infections, and seizures, necessitate vigilant postoperative care and monitoring. The epidemiology of EDH and SDH in the context of traumatic brain injury underscores their prevalence and the significant impact they have on the pediatric population. The successful management of this case, with both immediate surgical intervention and comprehensive postoperative care, illustrates the effectiveness of current treatment protocols. This case also sheds light on the critical need for a multidisciplinary approach in the long-term rehabilitation of pediatric patients, ensuring optimal recovery and development post-injury. In conclusion, this report contributes to the understanding of the management of traumatic brain injuries in children, emphasizing the significance of timely surgical intervention, careful monitoring for complications, and the importance of a holistic approach to patient care for favorable outcomes.